Elimination of scan blindness of microstrip array by using I‐shaped λ/2 resonator. Issue 2 (February 2014) - Ghosh, Chandan Kumar; Parui, Susanta Kumar
ABSTRACT A compact I‐shaped λ/2 resonator is introduced in order to reduce the mutual coupling between antenna elements and eliminate the scan blindness in a microstrip array. The proposed λ/2 resonator is inserted between the adjacent E‐shaped microstrip antenna elements separated by 0.45 λ, as a technique to suppress the occurrence of radiation in the horizontal direction. Simulated and measured results show that a reduction in mutual coupling of 35 dB is obtained between elements at the operation frequency of 3.94 GHz of the array. The scan properties of microstrip array with and without resonator have been studied and the result indicates that the scan blindness of the array can be well eliminated because of the effect of the resonator. We have developed experimental models that have proved this concept of scan blindness elimination. Finally, the influence of other antenna parameters at the presence of resonator in the array system has been studied. Prototype antennas of two‐element and four‐element array with and without resonator have been fabricated, measured, and the idea has been verified. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:334–338, 2014